Clear Cell Carcinoma of the Endometrium: Evaluation of Prognostic Parameters in 27 Cases - Zhang, Zhiyang; Gao, Penglian; Bao, Zhengqi; Zeng, Linggong; Yao, Junyi; Chai, Damin; Li, Tian (Frontiers in Oncology, 2021)
Objective: Clear cell carcinoma (CCC) of the endometrium is an uncommon yet aggressive tumor. Few cohort studies are reporting the overall survival time of CCC patients. This study aimed to retrospectively analyze the clinicopathologic features, molecular characteristics and survival data of 27 endometrial CCC patients to improve the understanding of CCC. Methods: The clinicopathologic features, molecular characteristics and survival data total of 27 CCC patients admitted to the BBMU affiliated hospital (Anhui, China) between January 2005 and December 2018 were retrospectively analyzed. Kaplan-Meier method was used to analyze the prognosis-related factors. Results: The median age of the patients was 60 years (range; 39 to 81 years). The average tumor size was 3.8 cm (range; 0.8 to 13.0cm). Myometrial infiltration greater than 50% was reported in 55.6% of the patients, while the Ki-67 index greater than 50% was reported in 70.4% of the patients. The patients’ FIGO (2009) surgical stages were as follows: 18 Ⅰ, 3 Ⅱ, 4 Ⅲ, and 2 Ⅳ. Besides, 7 (25.6%) patients had lymphovascular invasion, 3 (11.1%) patients with distant metastasis, including 1 patient with bone metastasis, and 2 with liver metastasis. Adjuvant treatment included 7 with chemotherapy alone, 9 with radiotherapy alone, and 9 with both radiotherapy and chemotherapy. The median overall survival time from the time of CCC diagnosis was 56 months. ER and PR showed negative expression and P16 showed patchy immunostaining. 18 (63%) cases showed Napsin A positive expression. Loss of MSH2, MSH6 and PTEN were seen in 5, 4 and 7 cases respectively. All cases showed HER-2/nue negative expression. Conclusion: CCC is a rare and invasive tumor. Age of diagnosis, FIGO stage, tumor size, myometrial infiltration, lymphovascular invasion, distant metastasis, Ki-67 index and P53 expression are important indicators to evaluate patient’s prognosis (P = 0.048, P < 0.001, P = 0.016, P = 0.043, P = 0.001, P < 0.001, P = 0.026, and P = 0.007, respectively). CCC has a worse prognosis than endometrioid carcinoma (P = 0.002), and there is no significant difference when compared with uterine papillary serous carcinoma (P = 0.155).